Particularized Conversational Implicature in the Movie Crazy Rich Asians (2018) by Jon M. Chu - Fatimah Syahidah; Mahi Mamat Hkikmat; Toneng Listiani (Journal of English Language and Education, 2026)
Particularized conversational implicature plays an important role in indirect communication because meaning can only be interpreted through specific contextual conditions. In socially structured interaction, speakers often rely on implied meaning rather than direct expression, especially when communication involves hierarchy, interpersonal tension, cultural expectation, and relational sensitivity. These patterns can be observed in the film Crazy Rich Asians (2018), where indirect communication frequently emerges through the flouting of conversational maxims. This research employed a qualitative descriptive method. The data consisted of 22 utterances containing particularized conversational implicature collected from film dialogues, scripts, subtitles, and repeated observation of relevant scenes. The data were analyzed using Grice’s theory of conversational implicature and conversational maxims. The findings show that particularized conversational implicature is generated through the flouting of the maxims of Quantity, Quality, Relation, and Manner. The implied meanings identified in the interactions depend heavily on contextual interpretation and cannot be understood solely through literal meaning. The study also reveals that indirect communication functions as an interactional strategy for managing hierarchy, regulating interpersonal tension, avoiding confrontation, and negotiating social relationships. Overall, the findings highlight that particularized conversational implicature operates not only as a pragmatic phenomenon, but also as a context-dependent interactional mechanism shaped by social and cultural dynamics.